2011
DOI: 10.1002/jso.22075
|View full text |Cite
|
Sign up to set email alerts
|

High rate of solitary sentinel node metastases identification by fluorescence‐guided lymphatic imaging in breast cancer

Abstract: Fluorescence-guided imaging using fluorescence retention detection allows transcutaneous navigation with a high rate of solitary positive SLN identification as an alternative technique for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…per groin, range [4][5][6][7][8][9][10][11][12][13][14], of which 109 were SLNs (mean 2.2 nodes (SD 1.4) per groin, range 1-7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…per groin, range [4][5][6][7][8][9][10][11][12][13][14], of which 109 were SLNs (mean 2.2 nodes (SD 1.4) per groin, range 1-7).…”
Section: Resultsmentioning
confidence: 99%
“…[8] This figure drops to 5 per cent in China and is minimal in the rest of the world. [9] This has led to interest in the development of novel techniques not reliant upon radioisotopes (our Lancet reference in press -will be published by the time this is accepted) which are currently restricted uptake of dye by higher echelon nodes [10][11][12] and high false negative rates. [13] (This seems a nonsequitur -what does it mean?)…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, since 2010, ICG was applied to SLN detection in breast cancer patients in over 40 studies and the detection rates were almost over 95 % [22,[25][26][27][28][29][30]. Some investigators compared the detection rates between ICG, blue dye, and nuclein and noticed the better performance of ICG compared with the blue dye and nuclein.…”
Section: The Developing Stagementioning
confidence: 99%
“…Some investigators analyzed the false-negative rate of ICG in SLNB and found it to be lower than 10 % [22,24,[26][27][28][30][31][32][33]. A meta-analysis of six studies, which used ICG as a tracer in SLNB of breast cancer patients, reported the sensitivity of about 92 % (85 %-96 %) and the specificity of about 100 % (97 %-100 %) [34].…”
Section: The Developing Stagementioning
confidence: 99%
“…Recently, ICGI has been used to detect SLNs in breast cancer patients. According to the first studies, ICGI is able to find the same lymph nodes as conventional radiotracer [40][41][42][43][44][45][46][47][48][49][50][51]. Also, ICG has been combined with 99m Tc as a hybrid radiotracer, where it can be used to ease the detection of SLN, and to replace blue dye [52].…”
Section: Sentinel Lymph Node Biopsymentioning
confidence: 99%